2019
DOI: 10.1158/1078-0432.ccr-18-1959
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, Open-Label, Multicenter, Dose-escalation Study of the Oral Selective FGFR Inhibitor Debio 1347 in Patients with Advanced Solid Tumors Harboring FGFR Gene Alterations

Abstract: Purpose: To investigate tolerability, efficacy, and pharmacokinetics/pharmacodynamics of Debio 1347, a selective FGFR inhibitor.Patients and Methods: This was a first-in-human, multicenter, open-label study in patients with advanced solid tumors harboring FGFR1-3 gene alterations. Eligible patients received oral Debio 1347 at escalating doses once daily until disease progression or intolerable toxicity. Dose-limiting toxicities (DLT) were evaluated during the first 4 weeks on treatment, pharmacokinetics/pharma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…Several selective small-molecule FGFR inhibitors entered clinical development in the past few years and have shown responses in patients with FGFR signaling pathway aberrations in phase 1/2 clinical studies (14)(15)(16)(17)(18)(19)(20). However, the majority of these agents bind reversibly to the adenosine triphosphate (ATP)-binding pocket of FGFRs.…”
Section: Introductionmentioning
confidence: 99%
“…Several selective small-molecule FGFR inhibitors entered clinical development in the past few years and have shown responses in patients with FGFR signaling pathway aberrations in phase 1/2 clinical studies (14)(15)(16)(17)(18)(19)(20). However, the majority of these agents bind reversibly to the adenosine triphosphate (ATP)-binding pocket of FGFRs.…”
Section: Introductionmentioning
confidence: 99%
“… 32 In a recently published phase I study with debio 1347, RECIST responses were seen across tumor types and mechanisms of FGFR activation, that is, FGFR1-3 amplification, mutation and fusions. 33 35 Currently, two FGFR inhibitors have gained FDA approval: pemigatinib was approved in April 2020 for the treatment of advanced iCCA, whereas erdafitinib was approved for therapy-resistant urothelial cancers harboring FGFR2/3 genetic alterations. 36 In CCA, a phase I as well as a phase IIa study in Asian patients showed promising results for erdafitinib, but due to the low patient numbers the clinical data available thus far cannot be considered fully conclusive yet [ClinicalTrials.gov identifier: NCT01703481] and [ClinicalTrials.gov identifier: NCT02699606].…”
Section: Clinical Studies With Fgfr Inhibitors In Ccamentioning
confidence: 99%
“…Debio‐1347 is a small, oral molecule that selectively inhibits the ATP binding site of FGFR1–3 [38]. A phase I clinical trial evaluated the safety and antitumor activity of debio‐1347 in 58 patients with solid tumors including breast (21%), biliary tract (14%), bladder (10%), uterine (9%), squamous cell lung cancer (7%), gastric cancer (7%), prostate cancer (3%), and cervical cancer (3%) with known FGFR 1–3 alterations [39]. FGFR1 amplification was most common (40%), followed by FGFR fusion (21%), FGFR2 mutation (12%), and FGFR3 mutation (17%).…”
Section: Debio‐1347mentioning
confidence: 99%